2017
DOI: 10.1186/s12958-017-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial content, oxidative, and nitrosative stress in human full-term placentas with gestational diabetes mellitus

Abstract: BackgroundThe purpose of this study was to determine the mitochondrial content, and the oxidative and nitrosative stress of the placenta in women with gestational diabetes mellitus (GDM).MethodsFull-term placentas from GDM and healthy pregnancies were collected following informed consent. The lipid peroxidation (TBARS) and oxidized protein (carbonyls) levels were determined by spectrophotometry, and 3-nitrotyrosine (3-NT), subunit IV of cytochrome oxidase (COX4), adenosine 5′-monophosphate (AMP)–activated prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 31 publications
0
19
1
Order By: Relevance
“…Ageing is a natural process that occurs in all organisms, controlled by environmental, genetic and epigenetic factors which may result in the deterioration of cells and tissues causing impaired physiological function (54). Ageing not only reduces the capacity of the body to function at full capacity but is also linked to a wide variety of age-associated conditions such as Diabetes Mellitus, Cardiovascular disease, Parkinson's and Alzheimer's disease (18,62,114,117). These age-associated conditions are influenced by changes in multiple cellular processes, including telomere shortening, DNA damage, oxidative stress, inflammation, genomic instability and mitochondrial dysfunction, resulting in altered cellular signalling and impaired cell survival (Figure 2) (44,55,82).…”
Section: Mitochondria and Ageingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ageing is a natural process that occurs in all organisms, controlled by environmental, genetic and epigenetic factors which may result in the deterioration of cells and tissues causing impaired physiological function (54). Ageing not only reduces the capacity of the body to function at full capacity but is also linked to a wide variety of age-associated conditions such as Diabetes Mellitus, Cardiovascular disease, Parkinson's and Alzheimer's disease (18,62,114,117). These age-associated conditions are influenced by changes in multiple cellular processes, including telomere shortening, DNA damage, oxidative stress, inflammation, genomic instability and mitochondrial dysfunction, resulting in altered cellular signalling and impaired cell survival (Figure 2) (44,55,82).…”
Section: Mitochondria and Ageingmentioning
confidence: 99%
“…AMPK is directly activated following elevations of AMP through inhibited ATP production and can be modulated by the AMP:ATP ratio in cells (Figure 3). AMPK activity is higher in placentas complicated with gestational diabetes mellitus (GDM) and has also been linked to premature senescence in fibroblasts (114,147). In addition, energy status of the cell has been compromised through elevated AMP:ATP ratios in cells exposed to ischemia and hypoglycaemia, conditions that are influenced by biological age (60,61).…”
Section: Mitochondrial Bioenergeticsmentioning
confidence: 99%
“…As we all know, the placenta is an organ that provides nutrients and energy to the fetus. Studies have found that mitochondrial enzyme activity in skeletal muscle of pregnant women with GDM was reduced compared with normal pregnant women [41], and the expression levels of AMPK , a gene in placenta closely associated with mitochondrial phosphorylation and ATP production, were significantly elevated [42], and the mitochondrial morphology of syncytiotrophoblast cells was abnormal [43], strongly indicating that mitochondrial function might be impaired. Recently, Holland et al’s review of gestational complications considered that changes of mitochondrial number were not consistent and may increase or decrease in the same pathological course; the duration of the damage to the tissue may be the cause for it [44].…”
Section: Discussionmentioning
confidence: 99%
“…Nitrative stress rises by the third trimester in physiological pregnancy. In pathological conditions mentioned above, this elevation might appear earlier and can reach higher levels [13,14].…”
Section: Introductionmentioning
confidence: 91%